Performance evaluation of inexpensive composite copper/iron ore oxygen carriers produced by industrial granulation in chemical looping combustion of coke oven gas - Xinghe Liu; Xinhua Lai; Yandong Li; Cao Kuang; Haiying Zhao; Mengshuang Li; Rongchao Li; Panlei Wang; Jinchen Ma; Chaohe Zheng; Haibo Zhao (Fuel Processing Technology, 2025)
Chemical looping combustion (CLC) is a promising technology with the potential to achieve dual objectives of coke oven gas (COG) efficient utilization and reduction of CO2 emissions in the steel industry. In this work, two inexpensive composite oxygen carriers, CuFe20M (16 wt% copper ore, 64 wt% iron ore, 20 wt% montmorillonite) and CuFe20C (16 wt% copper ore, 64 wt% iron ore, 20 wt% cement), are prepared at a large scale by the extrusion-spheronization and hydroforming methods, respectively. Its combustion performance is comprehensively evaluated using coke oven gas as the fuel in a fixed-bed reactor. The results show that the selection of an appropriate reaction temperature significantly influences the performance of the oxygen carriers. The CH4 conversion of CuFe20M and CuFe20C reaches the maximum of 95.90 % and 96.72 % at 900 °C, respectively. The CO conversion is not sensitive to temperature change. Excessively high reaction temperatures (>900 °C) lead to a noticeable increase in carbon deposition, resulting in a decline in carbon capture efficiency. Increasing the fuel gas flow rate will suppress the carbon deposition and improve the carbon capture efficiency. Correspondingly, shortening the reaction time will lead to the decrease of CO2 yield. Long-period CLC tests of COG reveal that the hydroforming-derived CuFe20C oxygen carrier exhibits excellent stability and reactivity compared to the extrusion-spheronization-derived CuFe20M oxygen carrier. Under the optimal operating conditions, the average CH4 conversion and CO conversion of the CuFe20C are 98.24 % and 95.35 %, respectively. Moreover, CuFe20C exhibits higher CO2 yield, carbon capture efficiency, and lower carbon deposition. This work provides support for the application of inexpensive composite oxygen carriers (preferably, CuFe20C) in the CLC of COG.